Myocardial electrical instability score: clinical and prognostic significance - A. V. Frolov; T. G. Vaykhanskaya; O. P. Melnikova; A. P. Vorobev; A. G. Mrochek (Российский кардиологический журнал)
Aim. To develop and test a risk-stratification model for patients with coronary artery disease (CAD) and non-ischemic pathologies based on a computer analysis of electrical instability ECG markers.Material and methods. In the period from 2011 to 2018, the study included 1014 patients with CAD and non-ischemic pathologies. Depending on ventricular arrhythmia status, the analyzed cohort was divided into 3 groups: 1) 644 patients without lifethreatening ventricular tachyarrhythmias (-VTA), mean age 51,7±16,1 years; 2) 280 patients with clinically significant ventricular arrhythmias (+csVA): ventricular extrasystoles (VES) >1500/24 h, coupled VES >50/24 h or unstable ventricular tachycardia (uVT), mean age 46,7±14,0 years; 3) 90 patients with life-threatening ventricular tachyarrhythmias (+VTA): persistent VT (pVT), successful cardiopulmonary resuscitation (CPR), appropriate discharges by implanted cardioverter defibrillator (CVD), sudden cardiac death (SCD), mean age 46,8±12,7 years.Using the Intekard 7.3 software, ECG markers of myocardial electrical instability were analyzed: T wave alternation, QT interval and dispersion, fragmented QRS, spatial QRS-T angle, turbulence onset and slope, and heart rate deceleration/acceleration.Results. Statistically significant differences were found between the values of T wave alternation, QT interval, fragmented QRS and QRS-T angle in groups 1 and 3 (-VTA) and (+VTA), p<0,005.Personalized model was formed for predicting the risk of life-threatening VTA (primary endpoints: pVT, appropriate CVD discharges, CPR, SCD) in patients with CAD and non-ischemic pathologies (cardiomyopathy, channelopathy) in 5 years follow-up. Integral score of myocardial electrical instability is proposed as new quantitative parameter for risk stratification (sensitivity 75%, specificity 78%, accuracy 77%).Conclusion. The myocardial electrical instability score provides the individual assessment of the dynamic SCD risk. The Intekard 7.3 software is a simple, economic and accessible ECG tool for arrhythmia monitoring.